Pedagogical Beliefs of Pre-service Teachers towards Teaching Physical Science at the Secondary Level - Amlesh Kumar; Panda, B. N. (JOURNAL OF INDIAN EDUCATION, 2020)
The purpose of the study was to examine the pedagogical beliefs of preservice science teachers about the nature of teaching and learning physical science, understanding how the physical science subject should be taught and characteristics of a good physical science teacher at the secondary level. Descriptive survey with mixed method approach was followed for data collection and analysis. 97 pre-service science teachers of RIE, Bhubaneswar were the participants of the study. The findings showed that pre-service science teachers had strong pedagogical beliefs towards the nature of teaching and learning physical science, were sensitive towards the effective use of pedagogy in teaching physical science and had knowledge about the characteristics of a good physical science teacher at the secondary level.